2008
DOI: 10.1271/bbb.70698
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Epicatechin and Epigallocatechin Contents Respond to Water Stress in Tea [Camellia sinensis(L.) O. Kuntze]

Abstract: An experiment was conducted to determine the association of tea catechins to water stress in tea, with the objective of determining their suitability as indicators for predicting drought tolerance in tea (Camellia sinensis). The study consisted of six tea clones (BBK 35, TRFK 6/8, TRFK 76/1, TRFK 395/2, TRFK 31/30, and TRFK 311/287) and four levels of soil water content (38, 30, 22, and 14% v/v), which were arranged in a complete randomized design and replicated 3 times. The treatments were maintained for a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 30 publications
6
14
0
Order By: Relevance
“…The putatively annotated proteins for catechin trait were those associated with phenylalanine, tyrosine and tryptophan biosynthesis and carbon fixation, which are products for shikimate pathway (Maeda;Dudareva, 2012) and abiotic stress response (stomatal closure). Hence, it was in agreement with this study since previous reports have shown that catechins play a role as indicators of desiccation tolerance in tea plants (Cheruiyot et al , 2008). Aminotransferases have been shown to play a major role in a variety of metabolic pathways, including, amino acid biosynthesis and photorespiration.…”
Section: Discussionsupporting
confidence: 93%
“…The putatively annotated proteins for catechin trait were those associated with phenylalanine, tyrosine and tryptophan biosynthesis and carbon fixation, which are products for shikimate pathway (Maeda;Dudareva, 2012) and abiotic stress response (stomatal closure). Hence, it was in agreement with this study since previous reports have shown that catechins play a role as indicators of desiccation tolerance in tea plants (Cheruiyot et al , 2008). Aminotransferases have been shown to play a major role in a variety of metabolic pathways, including, amino acid biosynthesis and photorespiration.…”
Section: Discussionsupporting
confidence: 93%
“…The results presented in this study indicate a general trend of increase in levels of polyphenols in response to both biotic and abiotic stresses. These results are in line with the reports that indicate that plants produce a wide range of secondary metabolites such as polyphenols during their normal growth and that these levels often change in response to stresses [26][27][28][29]. These responses may be elicited by interactions with microbes, insect pests, the environment, or the farm management practices.…”
Section: Discussionsupporting
confidence: 90%
“…Green tea is comparatively healthier than black and Oolong tea. Literature also suggests polyphenols as potential indicators of drought tolerance in Camellia sinensis (Cheruiyot et al, 2007) because of variation of shoot epicatechin and epigallocatechin contents in response to water stress (Cheruiyot et al, 2008). Tea plants are grown in a wide range of latitudes in the world ranging from 45 N (Russia) to 30 S (South Africa) and longitude from 150 E (New Guinea) to 60 W(Argentina).…”
Section: Introductionmentioning
confidence: 99%
“…Growth and productivity of tea plants largely depends on their capacity to adapt to abiotic stress, namely temperature, drought, metal, and nutritional disturbances. Although the effects of some individual environmental factors on the tea plant are well documented (Handique and Manivel, 1990;Chakraborty et al, 2002;Panda et al, 2003;Upadhyaya and Panda, 2004a;Jeyaramraja et al, 2005;Sharma and Kumar, 2005;Cheruiyot et al, 2007;Cheruiyot et al, 2008;Upadhyaya et al, 2008;Yadavand Mohanpuria, 2009;Upadhyaya et al, 2011;Upadhyaya et al, 2012;Das et al, 2012;Gupta et al, 2012), the effects of interacting abiotic factors remain poorly investigated.Therefore, the objective of this review is to highlight the effects of drought, heavy metal stress, and their interaction on growth, water relationships, nutrient status, and antioxidative responses during abiotic stress and its recovery in the tea plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation